Cost assessment for healthy diet in the state of Penang, Malaysia - Saleem, Fahad; Hassali, Mohamed Azmi; Thanoon, Omar; Ahmad, Akram; Umair Khan, Muhammad (Journal of Pharmacy Practice and Community Medicine)
Background: Despite the critical peril of deteriorating well-being of the Malaysian population, there remains lack of information related to the cost assessment of eating a healthy diet. Within this context, the current study addresses the issue of affordability of healthy eating in Malaysia by calculating the direct cost of healthy eating options provided by the Malaysian Dietary Guidelines. Methods: The study was designed as a once-only, time-based walk-in survey. Three hypermarkets located in the center of the Penang city were targeted for data collection. The examples provided by the Malaysian Dietary Guidelines for a one-day menu for 1500, 2000 and 2500 kcal were used for cost calculation. Worksheets were used for data collection and the data was later transferred to SPSS v 18 for analysis. Based on the objectives of the study, the data was described descriptively and average spending for a month was calculated. Results: Healthy eating was reported ‘unaffordable’ as on average, an individual following a 1500 kcal menu needed RM 845.50 (US $191.50) each month in order to stay healthy. Furthermore, those following 2000 and 2500 kcal menu plan had to spend RM 1062.30 (US $240.75) and RM 1437.60 (US $325.80) to consume healthy diet respectively. Conclusions: Affordability shaped as a major barrier towards healthy eating in the state of Penang, Malaysia especially for households having low and middle income. The findings are of particular importance because the immediate and long-term consequences of unhealthy diet are comprehensive and can influence lifelong practices.
Keywords: Cost; Assessment; Healthy diet; Malaysia; Affordibility; Nutrition